2018
DOI: 10.1088/2040-8986/aadd1f
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal effect on transverse-magnetic photonic properties of periodic dielectric-metal stacks

Abstract: We study scattering of a transverse-magnetic electromagnetic wave by a stack of thin metal layers with the width comparable to the skin-depth of the electromagnetic field in bulk metal. We use a microscopic approach based on the Boltzmann kinetic equation, which makes it possible to describe not only the nonlocality of metal conductivity but also the diffuse interaction of charge carriers with the surfaces of the metal film. Solving the Maxwell equations with nonlocal current density, we compare the transmitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…To overcome this limitation, alternative first-principles and self-consistent homogenization theories have been proposed [33,34], introducing a dispersive behavior for the material response with respect to the spatial coordinates [35][36][37][38][39]. Here, we rely on the approach described in [40,41], where nonlocal constitutive relations have been suggested that capture effects due to a strong spatial dispersion (SSD).…”
mentioning
confidence: 99%
“…To overcome this limitation, alternative first-principles and self-consistent homogenization theories have been proposed [33,34], introducing a dispersive behavior for the material response with respect to the spatial coordinates [35][36][37][38][39]. Here, we rely on the approach described in [40,41], where nonlocal constitutive relations have been suggested that capture effects due to a strong spatial dispersion (SSD).…”
mentioning
confidence: 99%